Yield Response And Nitrogen Use Efficiency Of Wheat Under Different Doses And Split Application Of Nitrogen Fertilizer (Bangladesh Journal of Agricultural Research, 2011)
A field experiment was conducted at the central research farm of Bangladesh Agricultural Research Institute, Gazipur for two consecutive years to verify the yield response of wheat variety Prodip to different doses and split applications of N fertilizer to determine appropriate N dose and application method for increasing NUE and grain yield of wheat. The treatments comprised of 12 combinations of three doses of nitrogen (80, 100, and 120 kg/ha) from urea, which were assigned in the main plots and four methods of N splitting viz., application of all N as basal; 2/3rd basal plus 1/3rd as top dress at crown root initiation (CR1) stage; 1/2 basal plus 1/2 as top dress at CR1 stage; and 1/3rd basal with 1/3rd as top dress at CR1 plus 1/3rd as top dress at 1st node stage which were tested in the sub plots. Higher yield was achieved from N rate of 120 kgiha applied as three equal splits of one-third as basal during final land preparation, one-third as top dressing during CR1 and the rest one-third top dressing at first node stage. The yield advantage of wheat due to N treatments was attributed to higher thousand grain weight and spikes/m2. Nitrogen content in wheat grain and straw was not affected significantly by different N treatment and their combinations, whereas plant N uptake was significantly influenced by N rate and N splitting and also due to the interaction of N rate and N splitting. Total N uptake was maximum under N rate of 120 kg/ha applied as three equal splits as 1/3rd basal with 1/3rd as top dress at CR1 plus 1/3rd as top dress at 1st node stage. Split applications of sub-optimal dose of N (80 kg/ha) resulted in negative gain in apparent NUE, but split applications, especially three split applications (1/3rd basal, 1/3rd at CR1, and 1/3rd at 1st node stage) of higher dose of N (100 and 120 kg/ha) resulted in positive gain in apparent NUE. Keywords: Wheat grain yield; nitrogen management; N uptake and NUE DOI: http://dx.doi.org/10.3329/bjar.v36i2.9249 BJAR 2011; 36(2): 231-240